Brentuximab vedotin and radiotherapy for CD30-positive cutaneous T-cell lymphoma - a retrospective multicenter analysis - Schummer, Patrick; Glatzel, Caroline; Schrüfer, Philipp; Lawrenz, Ingulf; Dobos, Gabor; Wehkamp, Ulrike; Hüning, Svea; Stranzenbach, René; Nicolay, Jan Peter; Goebeler, Matthias; Wobser, Marion (Journal der Deutschen Dermatologischen Gesellschaft, 2025)
Background and Objectives While brentuximab vedotin (BV) and radiotherapy (RTx) are established treatment options for CD30-positive cutaneous T-cell lymphoma (CTCL), data on their simultaneous or sequential use regarding efficacy and tolerability remain scarce. In this retrospective analysis, we evaluated the combination of BV and RTx in patients with CD30-positive CTCL. Patients and Methods We included 14 CD30-positive CTCL patients from six German cancer centers receiving BV; RTx was initiated within a timeframe of 3 months prior/after BV treatment. RTx was mainly applied as a low-dose scheme. Results Adverse events of any grade occurred in 71% of patients, most commonly peripheral neuropathy, neutropenia, and radiodermatitis. Thirteen patients achieved a complete or partial remission as best overall response, however, 50% of all patients showed disease progression. At a median follow-up of 14.4 months, median progression-free survival was 12.0 months, with a 1-year rate of 34.0%. Conclusions The simultaneous or sequential use of RTx during BV treatment was feasible and well tolerated. Future randomized investigations are needed to identify the benefits of this combination treatment regimen as well as adequate dosing of BV and RTx in a prospective manner.
Gesehen am 13.02.2026